Social Integration Management Of Places Of Worship For Islam And Christian In Surakarta - Lilam Kadarin Nuriyanto (Analisa: Journal of Social Science and Religion, 2015)
The dynamics of religious life in Surakarta is an interesting topic to be studied. Although this city is labeled as the home of radical Islamic groups in one side, this town has developed inter-religious harmony. This can be seen from the existence of mosque and church that are build side by side,  to name among those are; a mosque of Al-Hikmah with a church GKJ Joyodingratan, and a mosque sami'na with a church GBI Prosperous Diaspora. This study uses a qualitative method. There are two main findings of this research. Firstly, there is  tolerance initiated by the religious leaders. Secondly, there is cooperation, mutual assistance, and mutual respect in conducting worship. Furthermore, there is an inclusive attitude in practicing their religion, a wise and open attitude in dealing with activities held between nearby places of worship.